Percepção das informações transmitidas pela mídia sobre a covid-19 e sua relação com o fatalismo causado pela pandêmica em estudantes universitários da cidade de Lima - Arias-chávez, Dennis; Postigo-zumarán, Julio E.; Cangalaya-sevillano, Luis Miguel (Nuances: estudos sobre Educação, 2020)
The present study aims to determine the relationship between the perception of the information transmitted by mass media about Covid-19 and the fatalism originated by the pandemic in university students of Lima city. The composition of the population was 6,500 students, from which it was extracted a sample of 655 subjects, 310 males and 345 females, with ages between 16 and 32 years old (mean of 19.50 and standard deviation of 3.08) extracted from the first two cycles of four private universities and one public university of the city of Lima, by virtual way, in June 2020. The study is of non-experimental design at the relational level. The result obtained shows that there is a relationship between the perception of the information transmitted by the media about Covid-19 and the fatalism caused by the pandemic. The Spearman correlation is 0.238. The effect size is 0.4978. The statistical power is 0.9542, and these results can be generalized to the entire population of university students in the city of Lima.